A Primer on R for Numerical Analysis in Educational Research - Prokop, Tricia R.; Wininger, Michael (Frontiers in Education, 2018)
Researchers engaged in the scholarship of teaching and learning seek tools for rigorous, quantitative analysis. Here we present a brief introduction to computational techniques for the researcher with interest in analyzing data pertaining to pedagogical study. Sample dataset and fully executable code in the open-source R programming language are provided, along with illustrative vignettes relevant to common forms of inquiry in the educational setting.